2021
DOI: 10.1021/acs.jpca.1c06169
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Photophysics of Tellurium-Substituted Uracils: Insights from Multistate Complete-Active-Space Second-Order Perturbation Calculations

Abstract: The photophysical mechanisms of tellurium-substituted uracils were studied at the multistate complete-active-space second-order perturbation level with a particular focus on how the position and number of tellurium substitutions affect their nonadiabatic relaxation processes. Electronic structure analysis reveals that the lowest several excited states are closely concerned with the n and π orbitals at the Te 7 −C 2 [Te 8 −C 4 ] moiety of 2-tellurouracil (2TeU) [4TeU and 24TeU]. Both planar and twisted minima w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…It has been previously shown as SOC values computed for the approved drug Foscan (5,10,15,20-tetrakis­( m -hydroxyphenyl)­chlorin) are quite small (2.4 × 10 –1 cm –1 ) but are still sufficient to trigger the energy transfer process. The insertion of a heavy atom in the molecular structure considerably increases SOCs and generally red shifts the absorption band. This positive effect is however countered by the occurrence of toxic effects generally due to their enhanced dark cytotoxicity. For this reason, sulfur or other atoms naturally present in tissues are being chosen as preferential heavier atoms to be inserted into potential drugs structures for PDT.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown as SOC values computed for the approved drug Foscan (5,10,15,20-tetrakis­( m -hydroxyphenyl)­chlorin) are quite small (2.4 × 10 –1 cm –1 ) but are still sufficient to trigger the energy transfer process. The insertion of a heavy atom in the molecular structure considerably increases SOCs and generally red shifts the absorption band. This positive effect is however countered by the occurrence of toxic effects generally due to their enhanced dark cytotoxicity. For this reason, sulfur or other atoms naturally present in tissues are being chosen as preferential heavier atoms to be inserted into potential drugs structures for PDT.…”
Section: Introductionmentioning
confidence: 99%
“…These crucial properties can be easily tuned by proper structural modification, including the use of heavy atoms to enhance ISC or choosing appropriate ligands to modify the photophysical and electronic properties. The search for metal-free and less-toxic solutions has led to consideration of more biocompatible main group elements to induce heavy atom effects [ 38 , 39 , 40 ]. Several intriguing investigations so far, carried out on chalcogen-modified nucleobases, demonstrated that exocyclic carbonyl oxygen replacement by either sulphur or selenium produce nucleobases able to generate singlet oxygen [ 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar twisted and planar paths were also theoretically proposed to be the possible electronic deactivation pathways in telluriumsubstituted uracils. 59 In the indirect path (Paths I and II), such efficient triplet generation benefits from the ultrafast formation of the S 1 state, and subsequently, inhibition of the non-radiative S 1 -S 0 channel and acceleration of the crossing from S 1 to triplet states originating from larger spin-orbit coupling and energetic closeness between S 1 and triplet manifold in the vicinity of the S 1 minimum. 14 However, intersystem crossing directly from a higher singlet excited state usually needs to compete with the internal conversion and other processes.…”
Section: Introductionmentioning
confidence: 99%